Effect of Ginkgo biloba administration to apoptosis in rat (Rattus novergicus) brain cells exposed to Plumbum - Muhammad Hamdan; Widjiati Widjiati; Priya Nugraha; Jovian Philip Swatan (Open Veterinary Journal)
Background: Lead (Plumbum/Pb) has been identified as a potential cause of Parkinson's disease as well as possibly contributing to disease progression. Ginkgo biloba extract has been widely used to prevent and treat stroke which prevents brain cell apoptosis and neuroinflammation. This has been shown to be beneficial in cognitive recovery in stroke incidents. Aim: This study aimed to determine the effect of Ginkgo biloba on the expression of Superoxide Dismutase (SOD), Malondialdehyde (MDA), and Apoptosis-Inducing Factor (AIF) in the brain cells of rats (Rattus novergicus) exposed to Plumbum. Methods: The experimental animals used were 36 male white rats divided into 4 groups with different treatments of Plumbum and Ginkgo biloba at varying doses for 42 days, after which the brains were collected for examination of SOD, MDA, and AIF expressions using immunohistochemical methods and analyzed using ANOVA and Duncan's test. Results: Plumbum administration caused a significant decrease in SOD expression and an increase in MDA and AIF expressions (p [Open Vet J 2024; 14(8.000): 2049-2056]